Jumps and Information Asymmetry in the US Treasury Market - Ana-Maria Dumitru; Giovanni Urga (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyses the informational role of the trading activity when jumps occur in the US Treasury market. As jumps mark the arrival of new information to the market, we explore the contribution of jumps in reducing the informational asymmetry. We identify jumps using a combination of jump detection techniques. For all maturities, the trading activity is more informative in the proximity of jumps. For the 2- and 5-year maturities, there is a lower level of information asymmetry before the jump, followed by a high level during the jump window and up to 20 minutes after the jump occurs. Thus, the incorporation of new information in prices is not instantaneous but several transactions are needed for the market to completely acknowledge the new information. Finally, we propose the use of the estimated integrated volatility as an exogenous predictor of jump occurrence in addition to announcement surprises.
Keywords: G12; G14; C01; C51; 330; Jumps; High Frequency Data; Jump Tests; US Treasury Market; Macroeconomic News; Information Asymmetry